A iniciativa privada em saúde e a Constituição de 1988 - Silva, Rodrigo Alberto Correia da (2006)
The access to health products and services is guaranteed by the Federal Constitution of 1988, that allows its supplying for both State and private initiative. Contrary to the constitutional determination we face a social crises once it is note everyone that have access to medicines and health plans that make accessible health treatments. The supply of those utilities by the State is much inferior of the need of the many miserable people that lives in Brazil. The work analyses the medicines and health plans price control that takes place in Brazil by the Medicines Chamber and by the National Supplementary Health Agency respecting the Brazilian economic order system created by the Federal Constitution of 1988 with the targets of population access increasing also mandatory according to the Federal Constitution of 1988. The Constitutionality analyses of those price controls is done through the study of the national legal system the economic analyzes of those markets and the relation between those two aspects of the study object. The work development includes the debate about public services and the State powers over the private renders of those services by permission or concession and the difference between them and the private agents that renders services non privative to the State. At the end the micro-economic aspects of the medicines and health plans are analyzed to understand the impacts and limits of the State Regulation on those and the of the price control mechanisms used today. The conclusion of the work is for the unconstitutionality of the prices control by offending the free competition and free initiative principles, among others, and by being useless to fulfill the constitutional task for the State Regulation that is the increasing of the population acess to those prod ucts and services